Footstep manipulation during uphill running - Padulo, J.; Degortes, N.; Migliaccio, G. M.; Attene, G.; Smith, L.; Salernitano, G.; Annino, G.; D'Ottavio, S. (International Journal of Sports Medicine, 2013)
The present study investigated the effects of step frequency manipulation during training on slopes (2%) on biomechanical parameters at Iso-Efficiency Speed (without increasing the metabolic demand). 24 male marathon runners were randomly allocated to one of 2 training groups for 3 weeks: step frequency manipulation group (SFM, n=12) and free step frequency group (SFF, n=12). Lower limb kinematic parameters were measured before and after the 3 weeks training. The SFM group increased step length 4.30% (p<0.001), flight time 29.48% (p<0.001) and decreased contact time 14% (p<0.01). These findings coincide with characteristics of better running performances. The SFF group did not elicit such results. The results from the study could help coaches to devise training methods which could improve an athlete's performance through increasing step length. The method provided may aid faster race times for athletes.